The Practice of English Language Teaching - Harmer J. Jeremy (Harlow, Longman, 2007)
The highly acclaimed The Practice of English Language Teaching is an essential guide for teachers of English. The fourth edition has been completely revised to reflect new developments in language teaching. It includes: a discussion of English as a world language, an evaluation of new technologies in the classroom, a wide range of practical teaching ideas reflecting current methodological practice, an increased focus on issues such as: teacher development, learner autonomy and context-sensitive teaching, a DVD showing extracts from real classes and discussions between the author and the teachers.